Penerapan Model Pembelajaran Berbasis Proyek dalam Meningkatkan Motivasi Belajar Siswa di Kelas VIII [The Implementation of the Project-Based Learning to Improve the Grade VIII Students’ Learning Motivation] - Novelina Tobing; Cathryne Berliana Nainggolan (Diligentia: Journal of Theology and Christian Education, 2020)
Learning motivation is an important milestone for students since it provides the needed energy for students to achieve the learning goals with full attention and totality and to interpret the learning process that has been delivered through the learning activities. The purpose of this paper is to explore the implementation of the Project-based Learning model on student motivation in Grade VIII. The author's research subject is students in Grade VIII B, consisting of 13 students. The author uses research data from the results of the teaching’s portfolio and data triangulation (questionnaires, interviews, and observations). The findings of this research indicate that students’ motivation in Grade VIII B was improving. This improvement was shown through the indicators of student motivation during a series of teaching-learning processes in class. Through the implementation of the Project-based Learning model, teachers create learning environments and activities that are interesting, innovative, and relevant to the learning process of students in the classroom. Based on the results of the author's research, it is concluded that the implementation of Project-based Learning model can increase student motivation. The motivation to learn enables students to view and to participate in the learning process to be accountable to God as God's responsible co-workers. It is hoped that the teacher can apply the Project-based Learning model to help students with low learning motivation in class.